Sense and avoid considerations for safe sUAS operations in urban environments - Ince, Bilkan; Martinez, Victor Celdran; Selvam, Praveen Kumar; Petrunin, Ivan; Seo, Minguk; Tsourdos, Antonios (Institute of Electrical and Electronics Engineers (IEEE), 2024)
Operations involving small Unmanned Aerial Systems (sUAS) in urban environments are occurring ever more frequently as recognized applications gain acceptance, and new use cases emerge, such as urban air mobility, medical deliveries, and support of emergency services. The presence of Detect and Avoid (DAA) capability of sUAS is one of the major requirements for its safe operation in urban environments. The platform or its operator proves a full awareness of all potential obstacles within the mission, maintains a safe distance from other airspace users, and, ultimately, performs Collision Avoidance (CA) maneuvers to avoid imminent impacts. Communication and navigation defined scenarios are designed and performed within the simulation model in Systems Tool Kit (STK) software environment, covering several practical cases. The acquired data supports the assessment of feasibility and requirements for real-time processing. Utilizing Unreal Engine and MATLAB analysis of the findings and simulation results leads to a holistic approach to implementation of sUAS operations in urban environments, focusing on extracting critical DAA capability for safe mission completion. The proposed approach forms a valuable asset for safe operations validation, enabling better evaluation of risk mitigation for sUAS urban operations and safety-focused design of the sensor payload and algorithms.
Keywords: Detect and Avoid (DAA); small Unmanned Aircraft Systems (sUAS); Safety Operations; Risk Mitigation in Urban Environments